Method of Delineate of the ITCZ for the ITCZ Monitoring System Related to Early Season - Yulihastin, Erma; Fathrio, Ibnu; Cholianawati, Nani (LIPI Press, 2012)
The ITCZ has dominant of role to control atmospheric tropic-equator that were described clearly by satellite band of cloud and rain from west to east around the world as a part of Hadley circulation. Study the ITCZ phenomenon is very important because monsoon onset can be identifi ed by ITCZ jump to the northern or southern relative to the equator. Moreover, understand the ITCZ dynamic is keys to understand other phenomena such as ElNino Southern Oscillation (ENSO), Indian Ocean Dipole Mode (IODM), Madden Julian Oscillation (MJO), monsoon circulation, and Tropical Cyclone (TC). Other phenomena will disturb to the ITCZ. Study the ITCZ also important to predict rain and extreme event related to natural disaster such as fl ood, slide, dryness using prediction model. In this applied research, we develop monitoring system of the ITCZ based on MTSAT satellite observation to define early season over IMC (IMC). Research outputs are early season information and real time of ITCZ position on LAPAN website. The ITCZ position will always updated by real time. The information used to operational concern at LAPAN and researcher at other institutes for investigate early season predict to raise paddy fi eld productivity and to encourage development of early warning natural disaster system. Results show that jumping of the ITCZ positioncan be used to identify early season over IMC by global scale. Whereas in regional scale, jumping of the ITCZ appropriate to insitu observation to detect early season for monsoonal, equatorial, and local rain type. Moreover, time series profi le of the ITCZ has symmetry pattern with zonal wind over southern IMC.